2018
DOI: 10.1149/2.0311806jes
|View full text |Cite
|
Sign up to set email alerts
|

Migration of Ce and Mn Ions in PEMFC and Its Impact on PFSA Membrane Degradation

Abstract: The incorporation of cerium and manganese ions in perfluorosulfonic acid (PFSA) membranes strongly decreases the fluoride ion emission rate from fuel cell membrane electrode assemblies through their scavenging of reactive oxygen species generated during fuel cell operation. Concentration gradients of these ions and water fluxes lead to their migration and even loss from the fuel cell, but little is known about these phenomena that nevertheless impact proton exchange membrane fuel cell durability. We have deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
50
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(53 citation statements)
references
References 46 publications
2
50
1
Order By: Relevance
“…When Ce 3+ ions were introduced by spraying on both anode and cathode side (about 1% of SC-SO 3 H complexed), the same FER value of 1.6 Â 10 À9 mol cm À2 h À1 was measured. 41 Similar results were presented by Zatoń et al, 44 who observed a reduction of 2 orders of magnitude when loading the membrane with 0.04 mmol Ce 3+ g À1 membrane.…”
Section: Mitigation Of Fuel Cell Degradation With Cerium Saltssupporting
confidence: 83%
See 3 more Smart Citations
“…When Ce 3+ ions were introduced by spraying on both anode and cathode side (about 1% of SC-SO 3 H complexed), the same FER value of 1.6 Â 10 À9 mol cm À2 h À1 was measured. 41 Similar results were presented by Zatoń et al, 44 who observed a reduction of 2 orders of magnitude when loading the membrane with 0.04 mmol Ce 3+ g À1 membrane.…”
Section: Mitigation Of Fuel Cell Degradation With Cerium Saltssupporting
confidence: 83%
“…If this basic mitigation strategy is not possible, the number of reactive oxygen species can be reduced using radical scavengers. In the last two decades, various mitigation strategies have been investigated -an excellent overview is given in the review by Zatoń et al 5 Cerium serves either in its ionic form (Ce 3+ , Ce 4+ ) [41][42][43][44] or as solid cerium oxide (ceria, CeO 2 ) 45,46 as a radical scavenger. When ceria is incorporated into the membrane, it dissolves under operating conditions and produces both trivalent and tetravalent cerium ions.…”
Section: Mitigation Of Fuel Cell Degradation With Cerium Saltsmentioning
confidence: 99%
See 2 more Smart Citations
“…[7] When doping with additives such as metal oxides and chemical complexes comprising of certain metal and organic ligand components, membrane durability can dramatically be enhanced. [8][9][10][11][12][13][14][15][16][17] For example, Kjeang et al [15] reported that the lifetime of the MEA with additive CeO 2 was remarkably extended to 1,244 hours, demonstrating six times longer lifetime and 40 times lower fluoride emission rate than its baseline MEA without cerium. However, incorporating additives into proton exchange membranes is a double-edged sword.…”
Section: Introductionmentioning
confidence: 99%